Comparative analysis of central hemodynamics and physical performance in football players of various sports qualifications - Malakhova, S. N.; Малахова, С. М.; Малахова, С. Н. (Запорізький державний медичний університет, 2015)
Aim. To determine the infl uence of sports qualifi cation of football players on parameters of heart rate variability, central hemodynamics and physical performance. Methods and results. At the beginning of the preparatory period examination of 73 football players of various sports qualifi cations was carried out. It was established that relative value of physical performance and index of the functional state (IFS) are at a high enough level for all football players. That once again confi rms the orientation of the training process on the development of power-speed qualities with the appearance of a high-level general, speed and special endurance. Conclusion. Economization of physiological functions of qualifi ed football players manifested by bradycardia, prevalence of hypokinetic type of circulation (TC) and is lack in group of qualifi cation of MS and CMS athletes with hyperkinetic TC. З метою визначення впливу спортивної кваліфікації футболістів на параметри варіабельності серцевого ритму, центральної гемодинаміки та фізичної працездатності здійснили дослідження за участю 73 футболістів кваліфікації від II–III розрядів до майстра спорту України. Порівняли дані вегетативного забезпечення спортивної діяльності, центральної гемодинаміки, фізичної працездатності та індексу функціонального стану у футболістів залежно від спортивної кваліфікації. З’ясували, що оскільки за більшістю показників, які вивчили, між футболістами кваліфікації КМС і I розряд відсутні вірогідні відмінності, для коректності інтерпретації даних доцільно надалі формувати об’єднану групу, зокрема КМС–I розряд. С целью определения влияния спортивной квалификации на параметры вариабельности сердечного ритма, центральной гемодинамики и физической работоспособности провели исследование, в котором приняли участие 73 футболиста квалификации от II–III разрядов до мастера спорта Украины. Сравнили данные вегетативного обеспечения спортивной деятельности, центральной гемодинамики, физической работоспособности и индекса функционального состояния у футболистов в зависимости от спортивной квалификации. Установили, что покольку по большинству изучаемых показателей между футболистами квалификации КМС и I разряд отсутствовали достоверные различия, для корректности интерпретации данных целесообразно в дальнейшем формировать объединенную группу, а именно КМС–I разряд.
Порівняльний аналіз показників центральної гемодинаміки та фізичної працездатності у футболістів різної спортивної кваліфікації
Сравнительный анализ показателей центральной гемодинамики и физической работоспособности у футболистов различной спортивной квалификации
Keywords: football players; heart rate variability; central hemodynamics; physical performance; футболісти; варіабельність серцевого ритму; центральна гемодинаміка; фізична працездатність; футболисты; вариабельность сердечного ритма; центральная гемодинамика; физическая работоспособность